**Concept: The question tests on the basics of Algebra**

**Solution:**

Since x + 6 is a factor, putting x = -6 in the equation gives us:

(−6)^2+b∗(−6)−6=0

-6b - 6 + 36 = 0

-6b = -30

b = 5

**Option D**

Modified on: Tue, 12 Oct, 2021 at 1:33 PM

**Concept: The question tests on the basics of Algebra**

**Solution:**

Since x + 6 is a factor, putting x = -6 in the equation gives us:

(−6)^2+b∗(−6)−6=0

-6b - 6 + 36 = 0

-6b = -30

b = 5

**Option D**

Did you find it helpful? Yes No

Send feedbackSorry we couldn't be helpful. Help us improve this article with your feedback.

Help Desk Software
by Freshdesk Support Desk